2003
DOI: 10.1023/a:1023910315561
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In an attempt to eliminate similar item content as an alternative explanation for the relation between depression and rumination, a secondary analysis was conducted using the data from S. Nolen-Hoeksema, J. Larson, and C. Grayson (1999). After constructing a measure of rumination unconfounded with depression content, support for a two factor model of rumination was found. These analyses indicate that the 2 components, reflective pondering and brooding, differentially relate to depression in terms of predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,453
5
31

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 3,037 publications
(1,550 citation statements)
references
References 38 publications
61
1,453
5
31
Order By: Relevance
“…Rose et al, 2007), little was known about the personal characteristics that are potentially related to co-rumination. Drawing ideas from research on attachment, rumination, and trait depression, the current study attempted to demonstrate whether these personal characteristics, which have been found to be related to maladaptive emotion regulation strategies (Campbell et al, 2001;Schwartz-Mette & Rose, 2012;Treynor et al, 2003), would be related to co-rumination.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rose et al, 2007), little was known about the personal characteristics that are potentially related to co-rumination. Drawing ideas from research on attachment, rumination, and trait depression, the current study attempted to demonstrate whether these personal characteristics, which have been found to be related to maladaptive emotion regulation strategies (Campbell et al, 2001;Schwartz-Mette & Rose, 2012;Treynor et al, 2003), would be related to co-rumination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that people who possess a predisposition to trait depression may be more likely to engage in co-rumination. In fact, past research has found that depressed individuals tend to engage in emotion-focused coping strategies such as self-criticism, mental rumination, overt displays of distress, and wishful thinking (Mikulincer & Florian, 2004;Treynor et al, 2003). For this reason, the current study intends to conceptualize and examine depression as a stable characteristic, rather than a temporary way of feeling, and as a predictor of co-rumination.…”
Section: Trait Depression and Co-ruminationmentioning
confidence: 99%
See 3 more Smart Citations